Pendidikan Life Skill sebagai Upaya Menciptakan Kemandirian Santri di Pondok Pesantren al Urwatul Wutsqo Bulurejo Diwek Jombang - Arif Rahman Hakim (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2018)
Life skill educationis a formofal Urwatul Wutsqo boarding school anticipation in facing community problems. This boarding school has done many changes in educational process. The change is not only on Islamic education, but in educational life skill. The planning is started from determination of life skill, person in charge of the unit, grouping determination, life skill of preparation of activity report books. The purpose of life skill is fostering pupil to have independence, equiping pupil to have skill which useful for their future life. The method used is discussion, giving tasks, demonstration, giving good advice, giving story about succsessful and independence people. The independence must be achieved is emotional independence in fulfilling basic need, having independence attitude, capable in making decision. Evaluation verbally or directly, regular reports by the leader (Abah) either by phone or sending message, sending activity life skill books, direct observation of pupil, and life skill activities.